Global Proteomics Revealed Klebsiella pneumoniae Induced Autophagy and Oxidative Stress in Caenorhabditis elegans by Inhibiting PI3K/AKT/mTOR Pathway during Infection - Kamaladevi, Arumugam; Balamurugan, Krishnaswamy (Frontiers in Cellular and Infection Microbiology, 2017)
The enterobacterium, Klebsiella pneumoniae invades the intestinal epithelium of humans by interfering with multiple host cell response. To uncover a system-level overview of host response during infection, we analyzed the global dynamics of protein profiling in Caenorhabditis elegans using quantitative proteomics approach. Comparison of protein samples of nematodes exposed to K. pneumoniae for 12, 24 and 36 h by 2DE revealed several changes in host proteome. A total of 266 host-encoded proteins were identified by 2DE MALDI-MS/MS and LC-MS/MS and the interacting partners of the identified proteins were predicted by STRING 10.0 analysis. In order to understand the interacting partners of regulatory proteins with similar or close pI ranges, a liquid IEF was performed and the isolated fractions containing proteins were identified by LC-MS/MS. Functional bioinformatics analysis on identified proteins deciphered that they were mostly related to the metabolism, dauer formation, apoptosis, endocytosis, signal transduction, translation, developmental and reproduction process. Gene enrichment analysis suggested that the metabolic process as the most overrepresented pathway regulated against K. pneumoniae infection. The dauer-like formation in infected C. elegans along with intestinal atrophy and ROS during the physiological analysis indicated that the regulation of metabolic pathway is probably through the involvement of mTOR. Immunoblot analysis supported the above notion that the K. pneumoniae infection induced protein mis-folding in host by involving PI3Kinase/AKT-1/mTOR mediated pathway. Furthermore, the susceptibility of pdi-2, akt-1 and mTOR C. elegans mutants confirmed the role and involvement of PI3K/AKT/mTOR pathway in mediating protein mis-folding which appear to be translating the vulnerability of host defense towards K. pneumoniae infection.